THE EFFECT OF CAVITATION TREATMENT ON THE EXTINGUISHING OF PARTICLES OF OILS IN FUEL BOILERS - M. A. Taymarov; R. V. Akhmetova; S. M. Margulis; L. I. Kasimova (Известия высших учебных заведений: Проблемы энергетики)
The difficulties of burning the watered fuel oil used at the TPP as a reserve fuel for boilers are associated with its preparation by heating to reduce viscosity and the choice of a method of spraying with nozzles into the combustion zone. The quality of the preparation of fuel oil for combustion affecting the boiler efficiency is estimated by the length of the flame, the presence of burning large particles of fuel oil, the injection of coke and unburned particles onto screen and other heat-receiving surfaces. One of the ways to prepare fuel oil for combustion is cavitation treatment, which results in an emulsion consisting of fine micronsized particles. Heating of fuel oil particles after the nozzle in contact with the combustion zone is due to the flow of radiation from the burning torch. Therefore, in this article, the values of the flux density from the torch during the combustion of fuel oil are experimentally determined. The influence of particle size on the burning rate of the fuel oil M100 with the different density of the thermal radiation of the flame. It is found that the effect of cavitation treatment of fuel oil on the combustion rate is most significantly manifested in particle sizes less than 10 microns. For this purpose, the use of hydrodynamic cavitators are preferred at high fuel oil consumption rate.